METHOD OF FUNCTIONAL EVALUATION OF ADAPTATION OF VOLLEYBALL PLAYERS IN MICROCYCLES OF SPORTS TRAINING - Lutkov, V.F.; Miller, L.L.; Smirnov, G.I.; Shadrin, D.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the use of the method of variational pulsometry and electrocardiographic active orthotic test for individual assessment of the adaptation of highly qualified female volleyball players in training microcycles. Methods and structure of the study. The object of the study was 32 volleyball players of qualification from the 1st category to the masters of sports. Variational pulsometry (VP) was recorded under conditions of relative rest in microcycles of the preparatory and competitive periods. After registration of 100 R-R cycles (an indicator of the duration of the cardiac cycle), an active ECG orthotest was performed. Results and conclusions. In the course of studying the problem, it was revealed that heart rate indicators depend on the period of training and the nature of adaptation to training and competitive loads.